The effect of ticagrelor and clopidogrel on angiographic parameters according to diabetic status in patients with ST elevation myocardial infarction - F. Aydınyılmaz; H. Sunman; E. Algül; A. Ö. Özkaya İbiş; N. B. Özbeyaz; İ. Guliyev; M. Erzurum; T. Çimen; M. Tulmaç (Российский кардиологический журнал)
Aim. We aimed to compare post-interventional angiographic outcomes of ticagrelor versus clopidogrel according to glycosylated hemoglobin (HbA1c) levels in patients with ST-elevation myocardial infarction.Material and methods. The study included a total of 532 patients, with 334 receiving ticagrelor (62,8%) and 198 clopidogrel (37,2%). Diabetic status of the patients was assessed with HbA1c. TIMI flow grade and TIMI frame count were calculated and compared between two groups.Results. TIMI flow grade 3 was higher and TFC was lower after percutaneous coronary intervention of the infarct-related artery in patients treated with ticagrelor compared to clopidogrel (89,2% vs. 73,7%; p< 0,001, 20 vs. 24; p< 0,001). There was a positive correlation between the increases in HbA1c and TFC levels in the whole group (r=0,225; p=0,004). In subgroup analysis, higher HbA1c levels did not affect TFC in patients using ticagrelor (r=-0,060; p=0,326 for patients with noreflow, r=-0,133; p=0,321 for patients with TIMI-3 flow). While level of HbA1c did not affect TFC in patients with TIMI-3 flow, the presence of post-procedural no-reflow caused worsening of TFC in patients using clopidogrel as HbA1c levels increased (r=0,374; p=0,005).Conclusion. Ticagrelor was found to be better in terms of angiographic parameters regardless of diabetes.